Country Case Study: Sustainable Consumption and Production (SCP) in the Philippines. European Commission's SWITCH-Asia PROGRAMME - Leonardo L. Sta. Romana (Sustainable Asia: Supporting the Transition to Sustainable Consumption and Production in Asian Developing Countries, 2015)
This chapter examines the patterns of consumption and production in the Philippines and analyses their impact on the environment and climate, with a view to finding out whether they are environmentally sustainable or not. It presents the initial findings of the author's research on the topic of sustainable development in the Philippines. It notes the "double dividend" that the Philippines stands to gain from any action to "switch" consumption and production to more sustainable patterns.
Additional information: An edited (shorter) version of this paper appears as a chapter in SUSTAINABLE ASIA: Supporting the Transition to Sustainable Consumption and Production in Asian Developing Countries (World Scientific, Feb 2017). The e-book version can be accessed for free, with the compliments of the European Commission's SWITCH-Asia Programme, at: http://www.worldscientific.com/worldscibooks/10.1142/9862
Keywords: 330; Consumption; Production; Environment; Sustainability; Sustainable Development; Sustainable Development Goals; Developing countries; Philippines; South East Asia; Pollution; Climate change; Externalities